Autochthonous canine leishmaniasis in Romania: neglected or (re)emerging? - Mircean, Viorica (BioMed Central, 2014)
Canine leishmaniasis is a vector-borne zoonotic disease caused by the protozoan parasite Leishmania infantum. In Romania between 1955 and 2013, no cases of human autochthonous visceral leishmaniasis were reported. Data regarding canine leishmaniasis is similarly scarce. Since the first report of clinical autochthonous canine leishmaniasis in 1935, there were only three sporadic reports of positive dogs all without any clinical signs. Our study reports the first clinical case of autochthonous canine leishmaniasis in the last 80 years, stressing the importance of a targeted surveillance of Leishmania infection, as infected dogs act as the primary reservoir for zoonotic visceral leishmaniasis.